Protocol for a systematic review of psychological interventions for cancer-related fatigue in post-treatment cancer survivors - Corbett, Teresa (Syst Rev, 2015)
BACKGROUND: Fatigue is a common symptom in cancer patients that can persist beyond the curative treatment phase. Some evidence has been reported for interventions for fatigue during active treatment. However, to date, there is no systematic review on psychological interventions for fatigue after the completion of curative treatment for cancer. This is a protocol for a systematic review that aims to evaluate the effectiveness of psychological interventions for cancer-related fatigue in post-treatment cancer survivors. This systematic review protocol was registered with the International Prospective Register of Systematic Reviews (PROSPERO) database. METHODS/DESIGN: We will search the Cochrane Central Register of Controlled Trials (CENTRAL; The Cochrane Library), PubMed, MEDLINE, EMBASE, CINAHL, PsycINFO, and relevant sources of grey literature. Randomised controlled trials (RCTs) which have evaluated psychological interventions in adult cancer patients after the completion of treatment, with fatigue as an outcome measure, will be included. Two review authors will independently extract data from the selected studies and assess the methodological quality using the Cochrane Collaboration Risk of Bias Tool. DISCUSSION: Most existing evidence on cancer-related fatigue is from those in active cancer treatment. This systematic review and meta-analysis will build upon previous evaluations of psychological interventions in people during and after cancer treatment. With the growing need for stage-specific research in cancer, this review seeks to highlight a gap in current practice and to strengthen the evidence base of randomised controlled trials in the area. SYSTEMATIC REVIEW REGISTRATION: PROSPERO CRD42014015219.